ANALYSIS OF DETERMINING LOCATION INDUSTRY SUGAR FACTORY IN THE DISTRICT BLITAR - Alfa Chintya Anissa Haq (Socio-Economics/Agribusiness Department, 2017)
Location is an important part of social and economic activities of the concerned area by the proximity of one activity to another activity and the impact on these activities. In industrial activities, selecting the right location can have an impact on expenses both production costs and marketing costs. Development of the agricultural industry based on sugarcane and sugar as the main product is a strategic commodity. There are many sugarcane production in some areas still not been used by the sugar factorys. Capacity of sugar factorys that are still on a small scale led to these production of sugarcane being not fully used. One effort to utilize the production of sugar cane is to built a new sugar factory. This study aimed to analyze the deciding factorsof the sugar factory industry site selection and determine potential locations in Blitar. The analytical method used are factor analysis and factor rating. The results showed that the factors that affect the site selection of the sugar factory industry are spatial concentration factor, the factor of raw materials and infrastructure factors. Other potential sites for the construction of the sugar factory industry in Blitar including the District Nglegok, Ponggok, Binangun, Kanigoro and Wonotirto.